2020
DOI: 10.1371/journal.pone.0236734
|View full text |Cite
|
Sign up to set email alerts
|

Health and wellness coaching positively impacts individuals with chronic pain and pain-related interference

Abstract: Objectives Health and wellness coaching (HWC) interventions have been reported to improve health outcomes for individuals with chronic diseases such as diabetes, cardiovascular disease, or cancer. However, HWC also holds potential as an effective intervention within a biopsychosocial chronic pain management framework. The aim of the present study was to evaluate the effects of HWC on individuals with chronic pain. Methods Participants were referred by their primary care provider or insurance company to a compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Other published studies show that one-to-one phone-based health coaching using motivational interviewing (MI) skills, mindful listening, and goal setting support, has been associated with improved selfmanagement abilities, self-efficacy, health status, and medication adherence in a variety of chronic conditions including pain, diabetes, hypertension and hyperlipidemia and COPD. [37][38][39] The working alliance can predict patient adherence to treatment, in this case, coaching calls. 40,41 Learning engagement/communication skills like health coaching may be beneficial and synergistic to other interventions like pulmonary rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Other published studies show that one-to-one phone-based health coaching using motivational interviewing (MI) skills, mindful listening, and goal setting support, has been associated with improved selfmanagement abilities, self-efficacy, health status, and medication adherence in a variety of chronic conditions including pain, diabetes, hypertension and hyperlipidemia and COPD. [37][38][39] The working alliance can predict patient adherence to treatment, in this case, coaching calls. 40,41 Learning engagement/communication skills like health coaching may be beneficial and synergistic to other interventions like pulmonary rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Using a patient-oriented approach, health coaches help patients effect behavior change (e.g., alterations in diet and exercise) in order to improve their overall health and quality of life ( 10 ). One recent study that examined the effects of health coaching intervention in individuals with CNCP found clinically and statistically significant improvements in pain intensity and pain interference ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a small pilot study where health coaches provided approximately 24 sessions to 9 patients with fibromyalgia, patients showed clinically significant improvements in health-related quality of life, pain interference, and pain severity [ 21 ]. In a larger trial, health coaching was shown to lead to reduced pain intensity and pain-related interference among patients with chronic pain [ 22 ]. However, there are still relatively few studies examining the impact of health coaching on pain-CMI, and these early studies have not used an active control condition to control for the non-specific factors, such as attention from a caring provider.…”
mentioning
confidence: 99%
“…The preliminary empirical and theoretical support suggests the value in determining the efficacy of health coaching for pain-CMI [ 18 , 20 22 ]. The goal of the current manuscript is to present our protocol of a randomized controlled clinical trial for veterans with pain-CMI comparing remote-delivered health coaching to a remote-delivered active control, supportive psychotherapy, to reduce disability and determine mediators of treatment change.…”
mentioning
confidence: 99%